THE KNOWLEDGE MANAGEMENT GUIDELINES OF THE LOCAL CULTURAL HERITAGE OF SIM IN UPPER NORTHEAST OF THAILAND - Laddawan Sripachai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This research article aimed to explore the current condition of the Sim in the upper Isan region, investigate its tourism potential, and study the related cultural heritage knowledge management. The research is mix-method. Both qualitative and quantitative research approaches are employed by gathering the information from documents and field interviews with local wisdom, practitioners, and related people. The data was descriptively analyzed using the relevant theoretical framework. The results were as follows: The study of the tourism potential of the Sim in the upper Isan region indicated that the respondents had overall moderate opinions ( =3.07) about the tourism potential of the Sim in the upper Isan region. x ? When considering each aspect, every aspect was at a moderate level. The descending scores of each aspect were as follows: Reputation ( = 3.39), environment ( = 3.27), limitations of tourist capacity ( = 3.26), facilities ( = 2.97), ease of access ( = 2.90), and value of the tourist attractions ( = 2.60). In the management of knowledge about the cultural heritage of the Sim in the Upper Isan region, the findings were as follows: 1. For public relations, there was publicity through online media, which were the temple's Facebook Fanpage and other tourist attraction websites. 2. The database has only been established by government sections which were The Fine Arts Department and higher education institutes provided, but the temple has not had its own database yet. 3. The villagers and the temple have preserved the ancient temple site, and The Fine Arts Department has been responsible for the restoration and improvement. 4. The cultural landscape improvement has been made according to the original temple environment, and every part of the temple was harmonious. 5. In terms of management of cultural learning resources, tourists or those who were interested in studying the temple can go in and learn at any time by themselves since there has not yet been systematic management of knowledge in the Sim in the upper Isan region.